Structural Behavior and Design of Barrier-Overhang Connection in Concrete Bridge Superstructures Using AASHTO LRFD Method - Byungik Chang; Kamal Mirtalaei; Seungyeol Lee; Kenneth Leitch (Advances in Civil Engineering)
The U.S. Departments of Transportation adopted the AASHTO LRFD Bridge Design Specifications during the year 2007, which is mandated by AASHTO and FHWA. The application of LRFD specification initiated numerous research works in this field. This investigation addresses the LRFD and Standard design methodologies of concrete deck slab, deck overhang, barrier and combined barrier-bridge overhang. The purpose of this study is to propose a simplified manual design approach for the barrier-deck overhang in concrete bridges. For concrete deck slab overhang and barrier, application of National Cooperative Highway Research Program crash test is reviewed. The failure mechanism, design philosophy and load cases including extreme event limit states for barrier and overhang are discussed. The overhang design for the combined effect of bending moment and axial tension is probably the most important part of the design process. The overhang might be a critical design point of the deck with significantly higher amount of reinforcement. The design process becomes complicated due to combined force effect, LRFD crash test level requirement and the existence of several load combinations. Using this program, different LRFD load combinations are plotted together with the interaction diagram and the design is validated.